Schoolchildren thyroid volume in North Macedonia: data from a national survey in an iodine-sufficient country - Majstorov, Venjamin; Miladinova, Daniela; S. Kuzmanovska; Ittermann, T; Pop Gjorcheva, Daniela; Vaskova, Olivija; Ugrinska, Ana; Milevska Kostova, N; Karanfilski, Borislav (Springer Science and Business Media LLC, 2020)
North Macedonia is historically iodine deficient, but due to the longstanding and effective preventive measures, it has been considered iodine replete since 2003. The aim of the recent national survey was to re-evaluate iodine status and to measure thyroid volume (TVol) by ultrasound in schoolchildren as a representative of the general population.
Keywords: iodine deficiency, schoolchildren, North Macedonia, thyroid gland ultrasonography, thyroid volume